The Teachers and Parents Readiness in Implementing the Learning Based on BDR for Early Childhood Education During the Covid-19 in Banda Aceh - Hayati, Fitriah; Fitriani, Fitriani; Nurtaini, Ayi Teiri; Hanum, Cut Fazlil; Salmiati, Salmiati; Mutiawati, Yenni; Oktariana, Riza; Sari, Dewi Yuni (Jurnal Ilmiah Teunuleh, 2024)
This research was conducted to see to what extent the success of online program and BDR to early childhood. This research employed a descriptive qualitative method. The result revealed that teachers and parents are not completely able to accommodate the needs and the development of children, because not all of the developmenta spects could be tested through the assignment but also required routine habituation and a supportive environment. The parents also stated the dificulties in controlling the online learning, due several things such as the level of understanding in early childhood program, sometimes parents also need to control some online classes at the same time also because of parents’ busyness with another job including those parents who work outside of home. Three of six parents stated that difficulties in doing the activities based on the school curriculum demands, this is because the parents have different eaducational background with the teachers who already have enough competency in early childhood program. The parents usually will follow the teachers’ directions and even the children also not involved because of parents’ busyness and want to finish the assignment that given by the teacher to the children and sent back to the teacher based on the deadline that has been set. Based on the result of research towards the teachers stated that they have difficulty in applying learning from home system (BDR). In terms of parents, they also experience the same thing. Low the understanding of the children development make parents are difficult to do the activities that could stimulate all aspects of child development like the teachers did at school.